PENGARUH BRAND FEELINGS TERHADAP LOYALITAS TAMU DI SHERATON SENGGIGI BEACH RESORT LOMBOK - Ulumuddin, Ihya; Wibowo, Lili Adi; Barbo, Anthony (THE Journal : Tourism and Hospitality Essentials Journal, 2013)
Tourism is a service industry becomes global economic catalyst and a tool for socio-economic development. Tourism activities undertaken by tourists can not run if the lack of tourism products available to area attractions. The hotel is an integral part of the tourism business which is also a type of accommodation that uses some or all of the building to provide accommodation, food and beverage and other support services for the commercial general term. The level of competition-star hotel development in Sindh particularly in the area of Senggigi Beach and grow up. Sheraton Senggigi Beach Resort Lombok. Occupancy rates are important to describe the extent to which the number of rooms at the hotel was sold. Sheraton Senggigi Beach Resort Lombok strive to maintain and enhance the guests to come and stay back there, and the guests who had been a guest can be spiritual so that advocates can recommend it to others. The higher the level of competition in the hospitality industry to make the management aware that the need to make a strategy to achieve the target of loyalty costumer. Which an effort to maintain and enhance guest loyalty is to approach a good and harmonious relationship with the guests through emotional approach and the feelings of the guests to the brand (Brand Feelings). The purpose of this research is to discover the feeling of a brand that made Sheraton Senggigi Beach Resort Lombok, guest loyalty at Sheraton Senggigi Beach Resort and determine the effect of brand loyalty feelings towards guests at the Sheraton Senggigi Beach Resort Lombok. Theory brand feeling using Kevin L. Keller, guest loyalty while using Griffin. Object of this study is the guests who stay at the Sheraton Senggigi Beach Resort.Type descriptive research and verification, and the method used is an explanatory survey sampling with stratified random sampling technique, we obtained a population of 100 respondents. Techniques of data analysis and hypothesis testing used is Analyisis path (path analysis is). The results showed that feelings brand consisting of warmth, fun, excitement, security, social approval, and self-respect gives a significant impact on guest loyalty. As for suggestions for companies to maintain and enhance guest loyalty at the Sheraton Senggigi Beach Resort is through the development of brand feelings are more interesting, creative, innovative, effective and efficient.